2014
DOI: 10.1371/journal.pone.0089572
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Forest Biomass Carbon Storage in Liaoning Province of Northeast China: A Review and Assessment

Abstract: Accurate estimates of forest carbon storage and changes in storage capacity are critical for scientific assessment of the effects of forest management on the role of forests as carbon sinks. Up to now, several studies reported forest biomass carbon (FBC) in Liaoning Province based on data from China's Continuous Forest Inventory, however, their accuracy were still not known. This study compared estimates of FBC in Liaoning Province derived from different methods. We found substantial variation in estimates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
(31 reference statements)
0
13
0
1
Order By: Relevance
“…Furthermore, there were 72 vegetation plots in cold humid regions, 257 plots in temperate humid and semi-humid regions, 84 plots in temperate arid and semi-arid regions, 226 plots in warm temperate humid and sub-humid regions, 179 plots in north subtropical humid regions, 428 plots in mid-subtropical humid regions, 162 plots in south subtropical humid regions, and 63 plots in tropical humid regions. For the plots with only forest biomass, a coefficient of 0.5 was used to convert vegetation biomass density to C storage (Mg C ha −1 ; Cook et al, 2014;Yu et al, 2014). Unless the data of SOC storage (Mg C ha −1 ) were reported in the original studies, they were calculated using Eq.…”
Section: Data Collection and Compilationmentioning
confidence: 99%
“…Furthermore, there were 72 vegetation plots in cold humid regions, 257 plots in temperate humid and semi-humid regions, 84 plots in temperate arid and semi-arid regions, 226 plots in warm temperate humid and sub-humid regions, 179 plots in north subtropical humid regions, 428 plots in mid-subtropical humid regions, 162 plots in south subtropical humid regions, and 63 plots in tropical humid regions. For the plots with only forest biomass, a coefficient of 0.5 was used to convert vegetation biomass density to C storage (Mg C ha −1 ; Cook et al, 2014;Yu et al, 2014). Unless the data of SOC storage (Mg C ha −1 ) were reported in the original studies, they were calculated using Eq.…”
Section: Data Collection and Compilationmentioning
confidence: 99%
“…Implementing these large-scale programs not only improves the ecological environment, but also greatly helps local farmers and communities escape poverty in the program regions. Various case studies have demonstrated that these programs have substantially increased forest carbon stocks and sequestration rates at local levels (Chen and Hay 2009;Wang et al 2014;Yu et al 2014). However, there are few studies on quantification of the contributions of those large-scale programs to forest carbon stocks at regional and national levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent evidence shows that these constant BEFs are always the average values for a specific tree species, which are sometimes inaccurate given that stand age, stand density and site quality can change the BEFs (Lehtonen et al 2004, Teobaldelli et al 2009, Correia et al 2010. Thus, applying constant BEFs values across all age classes and site conditions within a forest type underestimates the forest biomass of younger or less productive stands or overestimates the forest biomass of older and more productive stands (Fang et al 1998, Goodale et al 2002, Yu et al 2014. In this study, the threshold stand volume where BEFs equal the constant BEF were 59, 39, 20 and 153 m 3 for CF, HB, SB and MP forests, respectively.…”
Section: Comparison Of Biomass Estimates From Different Methodsmentioning
confidence: 99%
“…Sharp et al (1975) estimated the regional forest biomass for Northern Carolina in the USA using a constant BEF of 2.0 Mg m -3 . However, more recent studies have indicated that the BEF is not a constant value and varies with forest age, site class and stand density (Fang and Wang 2001, Lehtonen et al 2004, Teobaldelli et al 2009, Correia et al 2010, Yu et al 2014. Thus, applying constant BEFs across all age classes and site conditions within a given forest type underestimates the forest biomass of younger or less productive stands and overestimates the forest biomass of older or more productive stands (Fang et al 1998, Goodale et al 2002.…”
Section: Introductionmentioning
confidence: 99%